Health-related quality of life in children with PFAPA syndrome - Claire Grimwood; Isabelle Koné‐Paut; Maryam Piram; Linda Rossi‐Semerano; Véronique Hentgen (2018)
Conventionally, PFAPA syndrome is considered as a benign disease compared to other recurrent fevers because it completely passes before adulthood. However, in our clinical practice, fever episodes have a huge impact on daily activities.Observational cohort study using the Pediatric Quality of Life Inventory (PedsQL™ 4.0) Generic Core and Fatigue Scales. PedsQL™ uses a modular approach to measure the HRQOL in children with acute and chronic health conditions. We used pediatric FMF patients as the control group.We included 33 children with PFAPA and compared them to 27 FMF patients matched for age: preschool-age children (2 to 7 years) and school-age children and youths (8 to18 years). PedsQL™ self-reported scores of children with PFAPA were systematically lower than those of FMF peers for general quality of life and physical and psychosocial functioning (significant only in the preschool-age group). PedsQL™ self-reported fatigue scores of children with PFAPA were significantly lower than those of FMF peers for both preschoolers and school-age children and youths. Parent proxy-reports were not significantly different, even though scores were systematically lower for the parents of PFAPA children.Our study demonstrates, for the first time, that the wellbeing of PFAPA children is poor, with a major impact on psychosocial functioning and increased fatigue. The quality of life of PFAPA children appears to be even lower than that of FMF patients, for whom a lower than normal HRQOL has already been demonstrated.